KONTEKTUALISASI AYAT HIDUP BERKUALITAS DAN MAKMUR PERSPEKTIF HERMENEUTIKA BATAS MUHAMMAD SHAHROUR - Muzakky, Althaf Husein (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2022)
Karl Marx's statement about religion as religion is opium is not necessarily correct. Religion in this case is the Qur'an that prioritizes a quality and prosperous life, through Muhammad Shahrour's hermeneutics, known as the boundary theory, can be a new idea. Through Shahrour's hermeneutical theory which is simplified into lower, middle, and upper limits, it is concluded that quality life has three personal levels by not bothering others, having material sufficiency, and having positive behavior. family level with sufficient material and family finances, managing the family on the right path, being socially sensitive to orphans and the poor. state level, maintaining state security, providing the best social contribution, one vision and mission in thinking about the nation